Penetrasi Pesantren terhadap Penetapan Perda Syari’ah di Tasikmalaya - Lindra Darnela (UIN Sunan Kalijaga Yogyakarta, 2015)
There are two major in the struggle discourse formalization of Islamic law. The first group is the pesantren leaders who agree with the formalization of Islamic law in Tasikmalaya district, while the second group is denied the formalization of Islamic law in Tasikmalaya. Patterns of thought and understanding of religious texts to be one of the basic choices attitude of the respective leaders of pesantren (Kyai). The attitude of the kyai in their support by signing in to be part of a successful team of the legislative and executive candidates who promised to bring forth specific regional regulations based on Islamic law. Whilst the attitude does not agree with the formalization of religion is silent and there are also other ways, such as by putting up banners that are not religious nuances to show disagreement to the formalization of religion in Tasikmalaya.